The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12876-016-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pancreatic serous cystic neoplasms: systematic review with a new case

Abstract: BackgroundThis study analyzes the clinicopathologic and radiologic characteristics of malignant serous cystic neoplasm (SCN) of the pancreas through systematic review and an institutional case report.MethodsA comprehensive literature search was performed in the MEDLINE database to identify studies on malignant SCNs of the pancreas that had detailed clinicopathologic and radiologic information. A computerized systematic search of our institutional database was also performed to identify cases of malignant SCN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…The number of IPMN tumours is slightly higher, which can be partially explained by the revised diagnoses after re-reviewing the histopathology. SCN tumours should only be resected when symptomatic, in case of rapid growth, if the diagnosis is uncertain or if there is concern about malignancy 17, 18,19 . However, imaging diagnostics of SCN is not always easy.…”
Section: Discussionmentioning
confidence: 99%
“…The number of IPMN tumours is slightly higher, which can be partially explained by the revised diagnoses after re-reviewing the histopathology. SCN tumours should only be resected when symptomatic, in case of rapid growth, if the diagnosis is uncertain or if there is concern about malignancy 17, 18,19 . However, imaging diagnostics of SCN is not always easy.…”
Section: Discussionmentioning
confidence: 99%
“…Huh et al 2 in a recent systematic review showed that these patients were between 42 and 87 years of age and the female to male ratio was 2.9. The most common symptoms or signs were abdominal pain (48%), palpable mass (22%), and weight loss (18%), and 11% of the patients presented an incidentally detected SCAc.…”
Section: What Is the Diagnosis?mentioning
confidence: 99%
“…Serous cystadenocarcinoma (SCAc) of the pancreas is a rare but well-established entity first described by George et al in 1989 1 , and since then less than 30 cases have been published 2 . The WHO classification defines it by the presence of distant metastasis, even if the primary tumor presents a benign histologic appearance 3 .…”
Section: What Is the Diagnosis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Seröse zystische Neoplasien wurden von den muzinösen Neoplasien erst 1978 durch Campagno et al [31,32] differenziert. Die ersten malignen SCN wurden 1989 von George et al [31,32] beschrieben. Histologisch ist die Wand der SCN von einer Reihe kuboidaler, glykogenreicher Epithelzellen, welche seröse Flüssigkeit produzieren, ausgekleidet.…”
Section: Seröse Zystische Neoplasie (Scn)unclassified